The Impact of Stock Liquidity on Firm Innovation: Evidence From China (Asian Journal of Social Science Studies, 2018)
Stock market has become a crucial financing channel for firms nowadays. As an important dimension of the characteristics of stock market, how will stock liquidity affect firm innovation? What are the underlying mechanisms? Those questions need to be explored further. Using Chinese non-financial A-share listed companies which had disclosed R&D expenditures in year 2006 to 2016 as the study sample, this paper investigates the effect of stock liquidity on firm innovation. The result shows that stock liquidity has a significant and positive effect on firm innovation. My finding is supported by additional test using Heckman sample selection model and several robustness tests. Further analysis shows that stock liquidity improves firm innovation by reducing financing constraints and increasing agency costs. This paper deepens the research on firm innovation from the perspective of market microstructure and owns implication for the government to encourage investment in R&D and will lead to develop multi-tiered capital markets.